The Influence of The Problem-Based Learning Model with A Problem-Posing Approach on The Analytical Ability - Eka Pramono Adi; Citra Kurniawan; Dina Ustifa (Jurnal Inspirasi Pendidikan, 2024)
Mathematics always includes numeracy skills and analytical skills related to problem-solving in everyday life. Applying the Problem-Based Learning model with the problem-solving approach aims to improve students' analytical skills to gain new knowledge to solve problems. This research uses a quantitative quasi-experimental method with a pretest-posttest control group design type. To find out the effect of applying this model, namely through a test instrument in the form of a written test or essay used to measure analytical abilities according to analytical ability indicators. The research results stated that applying Problem-Based Learning with the problem-solving approach significantly influenced students' analytical skills in mathematical numeracy. It is hoped that future researchers will be able to use research on the Problem-Based Learning model with the Problem-solving approach in a longer research period.